Efektivitas ZnOE, Ca(OH)2 dan Pasta Iodoform sebagai Bahan Pengisi Saluran Akar pada Perawatan Pulpektomi Gigi Sulung : Scoping Review - Rika Ridawanty; Naninda Berliana Pratidina; Risti Saptarini Primarti (Fakultas Kedokteran Gigi Universitas Hang Tuah, 2023)
Background: Dental caries is a disease that affects almost half of the world's population. A pulpectomy is an endodontic treatment by removing the entire pulp and filling the root canals of primary teeth using an appropriate root canal filling material. Root canal filling material becomes an indicator of the effectiveness of pulpectomy in primary teeth. Operators must comprehend various types of root canal filling materials available in primary dental pulpectomy treatments. Objective: This scoping review aims to obtain data on the effectiveness of ZnOE, Ca(OH)2, and Iodoform paste as root canal filling materials in pulpectomy treatment of primary teeth. Methods: This research was a scoping review. By using the PRISMA-ScR study, electronic database searches were conducted on PubMed, EBSCOhost, and Google Scholar. Results: A total of 89 articles were identified through a search on PubMed, 137 articles through EBSCOhost, 442 articles through GoogleScholar, and 48 articles through a search using Handsearching. The total number of articles identified through all the databases results in 716 articles. Using the PRISMA-ScR flow diagram to do the selection process, it results in seven articles that are eligible for review. Conclusion: As root canal filling materials in pulpectomy treatment for primary teeth, ZnOE, Ca(OH)2, and Iodoform paste were considered effective. The scoping review results in this study showed that Ca(OH)2 + Iodoform Paste (Metapex®) were better than ZnOE.